Surviving the host: Microbial metabolic genes required for growth of Pseudomonas aeruginosa in physiologically-relevant conditions - Belanger, Corrie R.; Dostert, Melanie; Blimkie, Travis M.; Lee, Amy Huei-Yi; Dhillon, Bhavjinder Kaur; Wu, Bing Catherine; Akhoundsadegh, Noushin; Rahanjam, Negin; Castillo-Arnemann, Javier; Falsafi, Reza; Pletzer, Daniel; Haney, Cara H.; et al. (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa, like other pathogens, adapts to the limiting nutritional environment of the host by altering patterns of gene expression and utilizing alternative pathways required for survival. Understanding the genes essential for survival in the host gives insight into pathways that this organism requires during infection and has the potential to identify better ways to treat infections. Here, we used a saturated transposon insertion mutant pool of P. aeruginosa strain PAO1 and transposon insertion sequencing (Tn-Seq), to identify genes conditionally important for survival under conditions mimicking the environment of a nosocomial infection. Conditions tested included tissue culture medium with and without human serum, a murine abscess model, and a human skin organoid model. Genes known to be upregulated during infections, as well as those involved in nucleotide metabolism, and cobalamin (vitamin B12) biosynthesis, etc., were required for survival in vivo- and in host mimicking conditions, but not in nutrient rich lab medium, Mueller Hinton broth (MHB). Correspondingly, mutants in genes encoding proteins of nucleotide and cobalamin metabolism pathways were shown to have growth defects under physiologically-relevant media conditions, in vivo, and in vivo-like models, and were downregulated in expression under these conditions, when compared to MHB. This study provides evidence for the relevance of studying P. aeruginosa fitness in physiologically-relevant host mimicking conditions and identified metabolic pathways that represent potential novel targets for alternative therapies.